2012
DOI: 10.1016/j.bbadis.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in neuronal L-type calcium channel activity in a double knock-in mouse model of Alzheimer's disease

Abstract: Increased function of neuronal L-type voltage-sensitive Ca2+ channels (L-VSCCs) is strongly linked to impaired memory and altered hippocampal synaptic plasticity in aged rats. However, no studies have directly assessed L-VSCC function in any of the common mouse models of Alzheimer’s disease where neurologic deficits are typically more robust. Here, we used cell-attached patch-clamp recording techniques to measure L-VSCC activity in CA1 pyramidal neurons of partially dissociated hippocampal “zipper” slices prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 43 publications
1
31
2
Order By: Relevance
“…Such results are generally similar to those described above for studies of normal aging in hippocampal neurons, in that Ca 2+ dyshomeostasis was in part manifested by altered CICR. On the other hand, in contrast to normal aging, hippocampal L-VGCC activity was recently found to be reduced in a transgenic AD model compared to wild-type controls, possibly because of Ca 2+ inactivation (Thibault et al, 2012). …”
Section: Neuronal Calcium (Ca2+) Dysregulation With Agingmentioning
confidence: 99%
“…Such results are generally similar to those described above for studies of normal aging in hippocampal neurons, in that Ca 2+ dyshomeostasis was in part manifested by altered CICR. On the other hand, in contrast to normal aging, hippocampal L-VGCC activity was recently found to be reduced in a transgenic AD model compared to wild-type controls, possibly because of Ca 2+ inactivation (Thibault et al, 2012). …”
Section: Neuronal Calcium (Ca2+) Dysregulation With Agingmentioning
confidence: 99%
“…Although in a separate study a change in the sAHP was not observed in pyramidal cells in a hAPP/PS1 Tg line, there was an increase in pyramidal excitability and altered sodium channel currents in these mice [37]. Interestingly, Thibault and colleagues [38] have recently reported a reduction in L-type calcium channel activity in the double knock-in hAPP/PS1 mice. These studies suggest that subtle changes in ion channel function are present in different AD Tg mouse lines that could impact on the ability of the network to generate network oscillations.…”
Section: Investigating the Causes Of Impaired Network Oscillationsmentioning
confidence: 93%
“…The altered activities of these enzymes may contribute to abnormal neuronal circuit functioning in such neuropathological conditions (Ji et al, 2009). Impairment in Ca 2+ homeostasis is a common feature in Alzheimer's disease and other neurodegenerative disorders involving damage and death of neurons (Mattson, 2007;Bezprozvanny and Mattson, 2008;Thibault et al, 2012 (Gargus, 2009). …”
Section: +mentioning
confidence: 99%